A food environments feedback system (FoodBack) for empowering citizens and change agents to create healthier community food places. (14th November 2017) - Vandevijvere, Stefanie; Williams, Rachel; Tawfiq, Essa; Swinburn, Boyd
Abstract: This study developed a systems-based approach (called FoodBack) to empower citizens and change agents to create healthier community food places. Formative evaluations were held with citizens and change agents in six diverse New Zealand communities, supplemented by semi-structured interviews with 85 change agents in Auckland and Hamilton in 2015–2016. The emerging system was additionally reviewed by public health experts from diverse organizations. A food environments feedback system was constructed to crowdsource key indicators of the healthiness of diverse community food places (i.e. schools, hospitals, supermarkets, fast food outlets, sport centers) and outdoor spaces (i.e. around schools), comments/pictures about barriers and facilitators to healthy eating and exemplar stories on improving the healthiness of food environments. All the information collected is centrally processed and translated into 'short' (immediate) and 'long' (after analyses) feedback loops to stimulate actions to create healthier food places. FoodBack, as a comprehensive food environment feedback system (with evidence databases and feedback and recognition processes), has the potential to increase food sovereignty, and generate a sustainable, fine-grained database of food environments for real-time food policy research.